Morphological effect on conductivity performance of ZnO/carbon nanotubes cotton hybrid - Md Yusof, Juraina; Ismail, Ismayadi; Yusop, Muhammad Rahimi; Abdul Rashid, Suraya (Elsevier BV, 2022)
Carbon nanotubes cotton (CNTC) is a bulk form of superfiber materials with soft, fluffy textures and light weight consisted of lengthy thread network of carbon nanotubes physically resembles cotton fiber used in textiles industry. We reported CNTC as a substrate and hybridization of ZnO nanostructures onto the CNTC surface. ZnO buffer layer for growth patterning localization was firstly deposited onto CNTC using 99.9% ZnO target. ZnO nanostructures were then attached on the CNTC substrate via chemical bath deposition method. It was observed that the average diameter and length of the nanostructures were increased resulting in highest aspect ratio of 12. Higher temperature at 120 ℃ gave the best conductivity of 7.8 S/cm. The synthesized nanostructures on CNTC are comparable to those synthesized on other substrate such as glass and alumina. In addition, this hybrid offers promising future as CNTC substate is flexible, readily available and low cost than those substrates.